Analysis of online surveys on endometriosis-symptoms, effects of treatment and how to treat the patient to cope with the disease - Misiło, Adriana; Sosna, Monika; Mordoń, Krzysztof (Journal of Education, Health and Sport, 2023)
Endometriosis is a complex disease syndrome characterized by chronic inflammation affecting mainly the pelvic organs. The etiopathogenesis is not fully understood. In the course of trying to understand the mechanisms that lead to the development of endometriosis, many hypotheses have been put forward, such as the theory of retrograde blood flow or the theory of metaplasia and induction. Endometriosis is the cause of many ailments and deterioration of the quality of life. In addition, it is an important factor in problems with getting pregnant and infertility. This paper is the summary of the survey results. The aim of the study to collect information of the awareness of the disease, methods of treatment and coping with ailments. The study was conducted via an online survey in the period from January to March 2020. The generated link [1], redirecting directly to the survey was placed on internet groups that gather women struggling with endometriosis. The results of the survey are presented below.